Cardiac complications associated with COVID-19: a single-center study from Southern Iran - Marjan Tariverdi; Mohammadbagher Rahmati; Maryam Mohammadian; Shahrokh Rajaei; Mohammadreza Kargarfard Jahromy; Niloufar Rahimi; Saeed Hosseini Teshnizi; Mohammad Tamaddondar; Shiva Badri; Hossein Abdollahi (Frontiers in Pediatrics)
BackgroundChildren account for a small percentage of COVID-19 cases and tend to exhibit milder symptoms compared to adults. Cardiovascular involvement has been observed in pediatric COVID-19 cases. This study aimed to determine the frequency of cardiac disorders in children hospitalized with COVID-19.MethodsThis cross-sectional study was conducted on pediatric patients admitted to Bandar Abbas Children Hospital, Iran, from March to September 2020. Patients with negative RT-PCR results for SARS-CoV-2, non-COVID-19 pulmonary involvement or pre-existing cardiovascular conditions were excluded. COVID-19 diagnostic subgroups were determined based on national guidelines. Clinical evaluations included chest CT scans to assess pulmonary involvement and cardiac assessments such as clinical symptoms, electrocardiography and echocardiography. Cardiac abnormalities were defined as clinical heart failure, dysrhythmias or abnormal echocardiography. Multivariable logistic regression was applied to analyze the associations between cardiac abnormalities, age and lung involvement, with statistical significance set at P < 0.05.ResultsThis cross-sectional study was conducted in 2020 on 475 children aged 1 month to 14 years. Among the participants, 48.4% had suspected, 30.5% had probable, and 21.1% had confirmed COVID-19. Cardiac abnormalities were identified in 35.2% of patients, including dysrhythmia (20.2%), heart failure (7.6%), and abnormal echocardiography findings (13.1%). The odds of cardiac abnormalities were 3.3 times higher in children with unilateral lung involvement and 5.9 times higher in those with bilateral lung involvement compared to those without lung involvement. Additionally, older age was associated with a 5.7% reduction in the odds of cardiac abnormalities.ConclusionsCardiac abnormalities in pediatric COVID-19 patients show a significant correlation with pulmonary involvement, highlighting their link to disease severity. Routine cardiac assessments may help identify complications and guide management, especially during sporadic cases and seasonal outbreaks.